Unilateral pulmonary hypoplasia: a rare clinical presentation. (20th March 2013) - Pathania, Monika; Lali, Bhagat Singh; Rathaur, Vyas Kumar
Abstract : The clinical presentation of an adolescent man with left lung hypoplasia is described in detail including the history and clinical examination findings. On further investigation, the chest x-ray and CT scan of the chest reveal interesting findings. Generally, such conditions are brought to notice in the early years of life but the presentation of this condition at the age of 18 years make it even more interesting and unique. This is a discussion of the management of such a patient and the different types of lung hypoplasia which can be encountered in clinical practice.